Interpreters in the United States Army Military Government in Korea: “A Government of, for, and by Interpreters”? - Kim, Hyongrae (TTR, 2021)
This paper will apply a Bourdieusian theoretical framework to analyze the military field and evaluate the interpreting habitus that emerged during the U.S. military occupation of South Korea (1945-1948). Despite its position of military dominance within the military field, the United States Army Military Government in Korea (USAMGIK) was unable to assert the normal hierarchical structure of an occupational force during interpreted events. This provided interpreters with the freedom to, when necessary, actively intervene in interlingual exchanges rather than be limited to function as “conduits.” This paper theorizes that interpreting activity is a site for the recontextualization of social hierarchical relations and proposes that while dominant agents and institutions typically dictate the terms under which the norms of interpreting are (re)established, under certain conditions, empowered interpreters may challenge the authority of these dominant institutions and redefine the interpreting habitus.